THE EFFECTIVENESS OF USING COOPERATIVE SCRIPT METHOD TO TEACH STUDENTSâ€™ SPEAKING ABILITY AT THE EIGHTH GRADE STUDENTâ€™S OF SMP NEGERI 1 BUAY BAHUGA - Rona Aulia Khumairoh (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2016)
The title of this study was the effectiveness of using cooperative script method to teach students speaking ability at the eighth grade studentsâ€™ of SMP Negeri 1 Buay Bahuga. The formulation problem of this study was â€œIs there any significant difference between the students who are taught by using Cooperative Script method and the students who are taught by using conventional method to teach speaking abilityâ€. And the objective of the study was to find out whether or not significance between the students who are taught by using Cooperative Script method and the students who are taught by using conventional method to teach speaking ability at the eighth grade students of SMP Negeri 1 Buay Bahuga in academic year 2015/2016. In this study was quantitative reseacrh, the writer used true experimental method and experimental design. Therefore, there were two groups those were control group who are taught using conventional method and experimental group who are taught using cooperative script, that was chosen by using cluster random sampling in collecting the data, the population of this study were 153 students and samples were 50 students. The data obtained from Independent ttest analysis by using SPSS 20, between the result of posttest in experimental group and control group. Based on the calculation by using Independent ttest in SPSS 20, the writer found that tobtained was higher than ttable (5.005 > 2.021) at the significant level Î±=0.05 in two tailed testing. It meant that there were any significant differences between experimental group and control group. So, the null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. It can be concluded that cooperative script method was significantly effective in teaching speaking ability at the eighth grade students of SMP Negeri 1 Buay Bahuga.